Becoming Wolf and other stories: using Indigenist arts-based methodologies to explore urban Indigenous coming of age. (September 2022) - Mellor, Andrea; Cloutier, Denise; Wang, Luyi; Kobayashi, Karen
Arts-based methodologies are increasingly being used in community-based research to explore and communicate issues of importance to Indigenous communities. Situating research in an Indigenist framework ensures that relational accountability—foundational to Indigenous ways of knowing and doing—is threaded throughout all stages of a research project. In this article, the authors describe how using Indigenist arts-based methodologies helped to develop critical knowledge sharing tools about urban Indigenous coming of age for youth living in foster care. The article describes how wisdoms gathered at a knowledge holder's dinner and two youth workshops were used to develop the story Becoming Wolf, which was later adapted to a watercolour infographic and a graphic novel. We hope that this article shows our support for socially transformative and allied research and contributes to discourses about knowledge co-creation and mobilization.